PERCERAIAN DI ERA DIGITAL: KASUS PERSELINGKUHAN MENJADI TREN DI MEDIA SOSIAL DAN DAMPAKNYA - Avvyat Anantya; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The changing times that have occurred have brought changes that can be felt, such as with the existence of social media, and divorce is a phenomenon that has been happening for a long time, but in the digital era, with the existence of social media and easy internet access, divorce cases have increased. Divorce is a current phenomenon because of the partner's infidelity. Divorce news is very easy to consume for all social media users because in this digital era, the phenomenon of infidelity is easily recorded on social media, and many cases of husbands and wives divorcing occur among celebrities and artists who have many followers with certain goals, one of which is to provide support. This deterrent effect on couples who are having an affair seems to be a trend on social media which will definitely have a social impact. This research aims to explore divorce cases that occur due to infidelity circulating on social media such as Instagram, the causes of the victim posting the phenomenon of infidelity that happened to him and its impact on relationships and modern marriages.